2021
DOI: 10.3390/rs13132641
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Investigation of Radiometric Interactions between Snowfall, Snow Cover, and Cloud Liquid Water over Land

Abstract: Falling snow alters its own microwave signatures when it begins to accumulate on the ground, making retrieval of snowfall challenging. This paper investigates the effects of snow-cover depth and cloud liquid water content on microwave signatures of terrestrial snowfall using reanalysis data and multi-annual observations by the Global Precipitation Measurement (GPM) core satellite with particular emphasis on the 89 and 166 GHz channels. It is found that over shallow snow cover (snow water equivalent (SWE) ≤100k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
(102 reference statements)
0
0
0
Order By: Relevance
“…In our study, we observed that the presence of liquid water has a strong impact on the detection of snowfall (increasing the rate of false alarms), while we did not notice any impact from snow-cover depth. This may be due to the categorization of snow cover at the time of the overpass that was performed by the PESCA algorithm and used as input in SLALOM-CT. Another explanation could be that our algorithm can better discriminate the signal produced by snowfall from those due to surface-related or atmospheric effects, compared with the analysis carried out in [97], where the analysis focused on GMI high-frequency window channels only (89 and 166 GHz). Moreover, our analysis showed that SLALOM-CT error statistics were almost independent of the surface category, which strongly affects the ground emissivity, as shown in Camplani et al [93].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we observed that the presence of liquid water has a strong impact on the detection of snowfall (increasing the rate of false alarms), while we did not notice any impact from snow-cover depth. This may be due to the categorization of snow cover at the time of the overpass that was performed by the PESCA algorithm and used as input in SLALOM-CT. Another explanation could be that our algorithm can better discriminate the signal produced by snowfall from those due to surface-related or atmospheric effects, compared with the analysis carried out in [97], where the analysis focused on GMI high-frequency window channels only (89 and 166 GHz). Moreover, our analysis showed that SLALOM-CT error statistics were almost independent of the surface category, which strongly affects the ground emissivity, as shown in Camplani et al [93].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Takbiri et al [97], it was shown that the liquid water content of clouds and the snow-cover depth impact the observed BT signals in high-frequency channels and can mask the relatively small signal due to snowfall. In particular, the emission due to liquid water tends to enhance the BTs, while a deeper snow cover tends to lower the surface emissivity, and these effects tend to mask the scattering signal produced by snowflakes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the snow depth, snow density and grain size of a snowpack on the surface complicates the retrieval of falling snow from passive microwave observations. Takbiri et al [159] related the precipitation scattering signal to the snow water equivalent of the snow cover and the liquid water path of the atmosphere. They highlighted a blind spot for a snow cover water equivalent above 200 kg m −2 and a liquid water path greater than 100-150 g m −2 where the microwave scattering signal was completely masked by the high emissivity of the surface and the liquid water content in snow clouds.…”
Section: Detecting and Quantifying Falling Snowmentioning
confidence: 99%